Different Incidence of Early-Onset Gastric Carcinoma Depending on Ethnicity: Preliminary Results of a Hospital in Liangshan. (10th March 2020) - Li, Shen; Rexin, Peter; Qin, Zhang; Changbo, Chen; Guanghui, Chen; Luyao, Wang; Voelker, Hans-Ullrich; Stauch, Gerhard
Abstract : Background . In China, the incidence of cancer has significantly decreased over the last two decades. In contrast, the incidence of gastric carcinoma (GC) has risen in young patients. Methods . We reevaluated the histopathological results of 4, 353 endoscopic gastroscopies from the Department of Pathology at No 1 Hospital of Liangshan. The ethnic groups Han and Yi were almost equally distributed in this cohort. Over a five-year period, 1407 GC were diagnosed. Results . In 171 of these cases (12%), the patients were ≤40 years old (early-onset GC, EOGC). Out of this cohort, 9 patients were aged ≤25 years. 54% of these patients were male and showed marked predominance (92%) of the Yi-minority. Using the classification of Lauren, 103 GC (60%) were of diffuse type, 27 (16%) of intestinal type, and 41 (24%) of mixed type. In the remaining 1, 236 cases of patients ≥41 years (88%), 1, 014 patients (82%) belonged to the Yi-minority. Helicobacter pylori (HP) were found in 46% of all cases. Familial clustering was found in 14 patients (18%; in first degree relatives, 12%, and in second degree relatives, 6%). Follow-up was not possible. Conclusion . This study demonstrates the unequal manifestation of EOGC within the two ethnic groups of Han and Yi. However, familial clustering was infrequent. Further investigations are necessary to discover relevant risk factors apart from hereditary predisposition.